An Analysis of Code Mixing and Code Switching on “Davyn Sudirdjo, Anak Indonesia Pencipta AI Untuk Pendidikan Helmy Yahya Bicara” Podcast - Jeni Ria Talu (CV. Publikasi Indonesia, 2026)
The increasing use of digital media has significantly influenced bilingual communication practices, particularly through platforms such as podcasts that provide spaces for spontaneous language interaction. In technology and educational discussions, speakers often combine Indonesian and English to express complex concepts, resulting in the emergence of code mixing and code-switching phenomena. This study aims to identify the types, forms, and functions of code mixing and code switching used in the podcast episode “Davyn Sudirdjo, Anak Indonesia Pencipta AI Untuk Pendidikan Helmy Yahya Bicara” This research employed a qualitative descriptive method. The data were collected by transcribing the entire podcast conversation and analyzing bilingual expressions based on Muysken’s (2000) theory of code mixing and Poplack’s (1980) theory of code switching. The findings reveal that code mixing occurred more frequently than code switching. A total of 23 instances of code mixing were identified, consisting of insertion (82.6%) and congruent lexicalization (17.4%), while alternation was not found. Meanwhile, 8 instances of code switching were discovered, including tag switching (50%), intra-sentential switching (37.5%), and inter-sentential switching (12.5%). The discussion indicates that English terms, especially those related to artificial intelligence and technology, were frequently incorporated to improve clarity, accuracy, and effectiveness in explaining specialized concepts. In conclusion, code mixing and code switching in the podcast function as strategic communication practices that support knowledge transfer, bilingual identity construction, and adaptation to global technological discourse.